2023
DOI: 10.31223/x5p93v
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-resolution grids of daily air temperature for Peru - the new PISCOt v1.2 dataset

Abstract: This study describes the development of PISCOt (v1.2), an innovative high-spatial resolution (0.01°) daily air temperature dataset for Peru (1981-2020). The development of PISCOt involves four main steps: i) quality control; ii) gap-filling; iii) homogenisation of weather stations; and iv) spatial interpolation. The methodological framework allows the representation of the complex spatial variability of air temperature at a more accurate scale than other national and global products (e.g. PISCOt v1.1, ERA5-Lan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 88 publications
0
9
0
2
Order By: Relevance
“…The hydrologic data used in the calculation are precipitation, evapotranspiration, and streamflow. The climate data were obtained from the gridded products PISCO ("Peruvian Interpolate Data of the SENAMHI's Climatological and Hydrological Observations") [21,22] and meteorological stations. The GCMs come from the NEX-GDDP [23], consisting of 21 models for the RCP scenarios 4.5 and 8.5.…”
Section: Data Collectionmentioning
confidence: 99%
“…The hydrologic data used in the calculation are precipitation, evapotranspiration, and streamflow. The climate data were obtained from the gridded products PISCO ("Peruvian Interpolate Data of the SENAMHI's Climatological and Hydrological Observations") [21,22] and meteorological stations. The GCMs come from the NEX-GDDP [23], consisting of 21 models for the RCP scenarios 4.5 and 8.5.…”
Section: Data Collectionmentioning
confidence: 99%
“…Many authors have argued that the lack of meteorological observations in the Peruvian Andes and the Amazonia is the main limitation for climate change impact studies (Andres et al, 2014; Aybar et al, 2019; Lavado Casimiro et al, 2011; Llauca, Lavado‐Casimiro, León, et al, 2021; Llauca, Lavado‐Casimiro, Montesinos, et al, 2021; Rau et al, 2018; Vegas Galdos et al, 2015; Zulkafli, 2014). To address this issue, Aybar et al (2019) and Huerta et al (2018) developed the Peruvian Interpolated data of SENAMHI's Climatological and hydrological Observations (PISCO) database, which is used in this study to force hydrologic model simulations. The PISCO database provides daily time series of precipitation, minimum and maximum temperature for the period 1981–2016, with a 0.1° horizontal resolution.…”
Section: Study Domain and Datamentioning
confidence: 99%
“…Precipitation time series in PISCOp (Aybar et al, 2019) were obtained using geostatistical and deterministic interpolation methods that include three precipitation sources: (1) the quality‐controlled and infilled national rain gauge dataset, (2) radar‐gauge merged precipitation climatologies, and (3) the Climate Hazards Group Infrared Precipitation (CHIRP) estimates. Daily time series of maximum and minimum temperature in PISCOt (Huerta et al, 2018) were obtained from: (1) observed maximum and minimum temperature data, (2) soil temperature product from the MODIS sensor (Moderate Resolution Imaging Spectroradiometer), and (3) geographic predictors (e.g., elevation, longitude, latitude and Topographic Dissection Index). The reader is referred to Huerta et al (2018) for full descriptions on the development of temperature products.…”
Section: Study Domain and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…La estimación de caudales de una cuenca es fundamental para la planificación del uso de los recursos hídricos, para la planificación agrícola y urbana así como para el dimensionamiento de las obras de infraestructura física, principalmente hidráulicas [1]. Referente a este último punto, el ingeniero muchas veces para estimar la magnitud de los caudales de diseño de las obras hidráulicas de protección y de aprovechamiento está obligado a utilizar métodos indirectos de lluvia-escorrentía [2], sobre todo cuando se carece de información hidrometeorológica que permita calcular volúmenes de agua con mediciones directas.…”
Section: Introductionunclassified